Comparative growth and biochemical composition of four strains of Nostoc and Anabaena (Cyanobacteria, Nostocales) in relation to sodium nitrate (2016)
Nitrogen concentration is an essential parameter in cyanobacterial cultures to produce enriched biomass with biotechnological purposes. Growth and biochemical composition of Nostoc LAUN0015, Nostoc UAM206, Anabaena sp.1 and Anabaena sp.2 were compared at 0, 4.25, 8.5 and 17 mM NaNO3. Cultures under laboratory conditions were maintained for 30 days at a volume of 500 mL. Anabaena sp.1 yielded the highest value of dry mass of 0.26 ± 2.49 mg mL-1 at 8.5 mM NaNO3. For chlorophyll, phycocyanin and phycoerythrin, maximum values were achieved at 17 mM NaNO3 with 18.09 ± 1.74, 102.90 ± 6.73 and 53.47 ± 2.40 μg mL-1, respectively. Nostoc LAUN0015 produced its maximum value of protein 644.86 ± 19.77 μg mL-1, and 890 mg mL-1 of carbohydrates in the absence of nitrogen. This comparative study shows that the most efficient strain for the production of protein, carbohydrates and lipids in diazotrophic conditions corresponded to Nostoc LAUN0015. However, Anabaena sp.1 and Anabaena sp.2 required high nitrogen concentrations to achieve higher values of metabolites, comparing with Nostoc strains. Nitrogen dependence for the production of pigments and high protein production in strains of Anabaena and in diazotrophic conditions for Nostoc was demonstrated. Nostoc can be cultured under nitrogen deficiency and Anabaena in sufficiency, for biomass production enriched with proteins and carbohydrates.